Between orality and literacy : communication and adaptation in antiquity - Scodel, Ruth, editor of compilation. (Mnemosyne, Supplements, 2014)
The essays in Between Orality and Literacy address how oral and literature practices intersect as messages, texts, practices, and traditions move and change, because issues of orality and literacy are especially complex and significant when information is transmitted over wide expanses of time and space or adapted in new contexts. Their topics range from Homer and Hesiod to the New Testament and Gaius' Institutes , from epic poetry and drama to vase painting, historiography, mythography, and the philosophical letter. Repeatedly they return to certain issues. Writing and orality are not mutually exclusive, and their interaction is not always in a single direction. Authors, whether they use writing or not, try to control the responses of a listening audience. A variable tradition can be fixed, not just by writing as a technology, but by such different processes as the establishment of a Panhellenic version of an Attic myth and a Hellenistic city's creation of a single celebratory history.